Headache as a single clinical manifestation of a colloid cyst in the third ventricle - Valença, Marcelo Moraes; Farias, Helysânia Shádylla Santos de; Almeida, Laryssa Crystinne Azevedo; França, Cassia Luana dos Santos; Nobre, Karolyne Ernesto Luiz; Valença, Marcelo Andrade; Silva Júnior, Mário Luciano de Mélo; Valença, Luciana Patrízia Alves de Andrade (Headache Medicine, 2017)
Neuroimaging in Headache